Speech acts in EFL classroom interaction in speaking class - Thoyyibah, Luthfiyatun; Tarwana, Wawan; Melati, Mela (Side: Scientific Development Journal, 2024)
This study aimed to identify preferred speech act found in EFL classroom interaction in speaking class based on Searle’s theory of speech act classifications and figure out types of speech acts mostly used in in EFL classroom interaction in speaking class. This study applied qualitative descriptive research design on a eleven grades at an Islamic Senior High Schools in Ciamis. The data were collected through observation and interview. Then the data were transcribed and analyzed. From the observation, directives speech act is mostly produced by the teacher than the others speech acts. This can be seen from the high percentage of assertive speech act has 26 utterances (22%), expressive speech act has 19 utterances (16%), directive speech act has 53 utterances (45%), and commissive speech act has 21 utterances (17%). Regarding directive function, the teacher explained through an interview that, directive of commanding, asking, and requesting are used by the teacher. The function of command is to get students focused on learning when the teacher commands them to pay attention. The teacher used a asking to test the understanding of the students. The teacher employs a lot of request sentences in the core activities to get students to participate in their learning. Its purpose is to assess how far the students' knowledge or understanding has progressed